Spatial distribution of Legionella pneumophila MLVA-genotypes in a drinking water system. (15th June 2015) - Rodríguez-Martínez, Sarah; Sharaby, Yehonatan; Pecellín, Marina; Brettar, Ingrid; Höfle, Manfred; Halpern, Malka
Abstract: Bacteria of the genus Legionella cause water-based infections, resulting in severe pneumonia. To improve our knowledge about Legionella spp. ecology, its prevalence and its relationships with environmental factors were studied. Seasonal samples were taken from both water and biofilm at seven sampling points of a small drinking water distribution system in Israel. Representative isolates were obtained from each sample and identified to the species level. Legionella pneumophila was further determined to the serotype and genotype level. High resolution genotyping of L. pneumophila isolates was achieved by Multiple-Locus Variable number of tandem repeat Analysis (MLVA). Within the studied water system, Legionella plate counts were higher in summer and highly variable even between adjacent sampling points. Legionella was present in six out of the seven selected sampling points, with counts ranging from 1.0 × 10 1 to 5.8 × 10 3  cfu/l. Water counts were significantly higher in points where Legionella was present in biofilms. The main fraction of the isolated Legionella was L. pneumophila serogroup 1. Serogroup 3 and Legionella sainthelensis were also isolated. Legionella counts were positively correlated with heterotrophic plate counts at 37 °C and negatively correlated with chlorine. Five MLVA-genotypes of L. pneumophila were identified at different buildings of the sampled area. The presence of a specific genotype, "MLVA-genotype 4", consistently co-occurred with high Legionella counts and seemed to "trigger" high Legionella counts in cold water. Our hypothesis is that both the presence of L. pneumophila in biofilm and the presence of specific genotypes, may indicate and/or even lead to high Legionella concentration in water. This observation deserves further studies in a broad range of drinking water systems to assess its potential for general use in drinking water monitoring and management. Graphical abstract: Highlights: Legionella was abundant through all seasons in water and biofilm. Legionella pneumophila serogroup 1 was the predominant identified serogroup. When Legionella was present in biofilm its counts in water were >30 cfu/l. Five L. pneumophila MLVA-genotypes were identified at different buildings. MLVA-genotype 4, consistently co-occurred with high Legionella counts in cold water.